Pembinaan Orang Tua Peserta Didik Sebagai Upaya Penguatan Pendidikan Karakter Anak Usia Sekolah Dasar - Agnes Fibriana Kurniawati; Ria Triayomi; Ongko Handoko; Stefanus Setyo Wibagso; Petrus Murwanto (Jurnal Dehasen Mengabdi, 2026)
This Community Service (Pengabdian kepada Masyarakat/PkM) activity was conducted in response to the increasing number of domestic violence cases involving children, as well as the ongoing tendency of some parents to entrust character education entirely to schools. The program was carried out through an in-person parenting seminar at SD Indriasana Palembang on January 23, 2026. Attended by 38 parents/guardians of 1st to 3rd-grade students, the seminar discussed the characteristics of Generation Alpha, parenting challenges in the digital age, the importance of role modeling, positive communication, emotional support, and children's character building. The evaluation results showed that 86.8% of the participants found the activity to be highly beneficial. All respondents (100%) agreed that character education is a shared responsibility between schools and parents. The majority of respondents emphasized the importance of parental role-modeling, emotional support for children, and the cultivation of basic values such as honesty (76.3% strongly agreed), responsibility (71.1% strongly agreed), and politeness (73.7% strongly agreed). However, maintaining consistency in applying rules at home remains a challenge, as the proportion of those who "agreed" (60.5%) was higher than those who "strongly agreed" (39.5%). Additionally, 5.3% of the respondents have yet to support regular communication with teachers. Overall, this program successfully increased parental awareness and strengthened the synergy between school and home, producing a parental guidance module titled "Orang Tua Hebat" (Great Parents) as its output.